The nuclear field treatment of some exactly soluble models - Bés, Daniel; Broglia, R. A.; Dussel, G. G.; Liotta, R.; Sofía, H. M. (North Holland Publishing, 1976)
Fil: Bés, Daniel Comisión Nacional de Energía Atómica; Argentina